Considering Ethics in Dance, Theatre and Performance - Bannon, Fiona (Springer International Publishing, 2018)
This book asks important questions about making performance through the means of collaboration and co-created practice. It argues that we can align ethics and aesthetics with collaborative performance to realise the importance of being in association with one another, and being engaged through our shared imaginations. Evident in the examples of practice visited in this study is the attention given by a number of practitioners to the development of shared, co-operative modes of creation. Here, we can appreciate ethical work as being relational, forged in association with the others as we cultivate ideas that matter. In looking at a range of work from practitioners including Meg Stuart, Rosemary Lee, Deufert&Philschke and Fevered Sleep, Considering Ethics in Dance, Theatre and Performance explores ways that we rehearse by attending to ethics, aesthetics and co-creation. In learning to listen, to observe, to co-operate and to negotiate, these practitioners reveal the ways that they bring their work into existence through the transmission of shared meaning.